Multiple Positive Solutions for a Fractional Boundary Value Problem with Fractional Integral Deviating Argument. (15th July 2012) - Guezane-Lakoud, A.; Khaldi, R.
Abstract : This work is devoted to the existence of positive solutions for a fractional boundary value problem with fractional integral deviating argument. The proofs of the main results are based on Guo-Krasnoselskii fixed point theorem and Avery and Peterson fixed point theorem. Two examples are given to illustrate the obtained results, ending the paper.